UPAYA PENGEMBANGAN INVESTASI IKM BORDIR DALAM MENINGKATKAN PAD KABUPATEN DEMAK - Caroline, Caroline; Pamudji, Teguh; Syakur, Abdul (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2018)
In exercising regional autonomy as mandated by Law No 32 Year 2004 on Regional Government and Law No 33 of 2004 on revenue sharing and central and local government Act No 28 of 2009 on local taxes and levies Third Law implies that a region vying to dig and search for sources of local revenue. Embroidery Demak needed short-term investment plans, medium and long consequences of regional autonomy is not easy, considering an area diuntut must find alternative sources of financing region One source of financing in Demak is the presence of developing SMEs Embroidery located in several districts in Demak, however, there are three centers of IKM is District Bonang, Wedung, and Wonosalam IKM development Short-term investment plans annual 5 USD 5.715 billion; 10-year medium-term IDR 38.432 billion; Long-Term IDR 15 years Rp 258.461 billion and 20 years 1,738,204,000,000. There are 5 dimensions HPI Embroidery Demak need to be developed, namely: Finance, Accounting, Review HR, Production and Marketing Process. By positioning strategy: Rapid Growth for Financial Dimension; Stable Growth for Dimension Bookkeeping; Selective Maintenance for Human Dimension; Turn around for Dimensional Marketing; Concentric Diversification of Production Process dimension.